Effect of PG-600 dose in cows with persistent corpus luteum treated with PGF2α and hCG - Sofia Brenieta Brilianti; Sri Mulyati; Wurlina Wurlina; Budi Utomo; Oky Setyo Widodo (Ovozoa: Journal of Animal Reproduction, 2024)
The purpose of this study was to determine the effect of administering a dose of gonadotropin (PG-600) in cows with persistent corpus luteum (PCL) which were treated with prostaglandin F2 α (PGF2α) and human chorionic gonadotropin (hCG). This study used 20, three-year-old cows diagnosed with PCL, had recently given birth, and were not pregnant. Cows were randomly allocated into groups T0, T1, T2 and T3.  Cows in all groups were injected with PGF2α (25 mg/cow). Simultaneously, cows in groups T1, T2 and T3 were also injected with PG-600 at doses of 100, 150 and 200 IU/cow respectively. PGF2α and PG-600 were injected when PCL was identified. After that, cows showing signs of estrus were injected with hCG (100 IU/cow) and artificially inseminated 12-18 hours after the appearance of signs of estrus. AI was conducted using frozen thawed semen. Sixty days following AI, a pregnancy examination was conducted using USG. Estrus was detected in all treated cows, while the pregnancy rates varied. Compared with other groups, the groups given 100 and 150 IU PG-600 produced higher pregnancy rates. It could be concluded that the combination of 25 mg PGF2α, 150 IU PG-600, and 100 IU hCG was the most effective treatment to produce high pregnancy rates in cows with persistent corpus luteum.